Interdisciplinaridade e currículo da Educação Profissional: sentido e autoconhecimento - Neves, Cibele Cavalheiro (2018)
Considering the design of courses and curriculum of Professional Education of Senac São Paulo, this research was dedicated to describe the process of development, concomitantly, the trajectory of self-knowledge of the researcher, aiming to identify the possibilities of action and reflection of a pedagogical consultant to act in a way interdisciplinary in all stages of curriculum construction, contributing in a significant way in the expansion of possibilities of interdisciplinary intervention of the teachers, thus qualifying, the construction of students' knowledge. In the form of a continuous narrative, plotting the author's personal and professional life story and contributed in the Interdisciplinarity of Finance, the results verified demonstrate the importance of the triad Being, Belonging, Doing. In an analogous way, Uroboro, a guiding metaphor for this investigation, it was verified that Interdisciplinarity provides a connection of the Inner Self with the environment, with the work, with the family, with the discourse, enabling actions with meaning and meaning for those involved